Will talent attraction and retention improve metropolitan labor markets? The labor market impact of increased educational attainment in U.S. metropolitan regions 1990 - 2010 - Stuart Andreason (Federal Reserve Bank of Atlanta, 2015)
Since the early 1990s, metropolitan entities and local governments have targeted incentives, policies, and investments with the goal of highly educated and skilled workers to locate in their communities. These efforts focus on attracting workers who hold a bachelor's degree or higher and have had a profound effect on the form and management of metropolitan areas, but there is not clear evidence that growth in bachelor's or higher degree attainment improves metropolitan labor market outcomes. I use an outcomes-based cluster-discriminant analysis to test whether or not metropolitan areas with growth in bachelor's or higher degree (BA+) attainment from 1990 to 2010 that is above the national average experienced improvements in the local labor market. Increased BA+ attainment leads to two distinct set of local labor market outcomes: one in which earnings per job increases but inequality, unemployment, and poverty rates rise, and the other in which income inequality growth is low and unemployment and poverty rates decline but earnings per job are stagnant or negative. I find evidence that "educational segregation," restrictive land-use policies, crime, and changes in military employment all predict outcomes.
Keywords: J10; O21; R11; 330; educational attainment; metropolitan labor markets; labor market outcomes; talent attraction and retention